Designing Adaptive Virtual Worlds - Gu, Ning (De Gruyter, 2014)
Designing adaptive virtual worlds takes the design of virtual places for education, entertainment, online communities, business, and cultural activities to a new level. This book presents an agent model for a design grammar so that unique places can be created responding to the changing needs in the virtual world. Applying these techniques has immediate implications on the design of games
Description based on publisher supplied metadata and other sources
Keywords: Human-computer interaction; Multimedia systems; Virtual reality; Design; Virtuelle Realität